Feature Papers - Michael Henson (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
This special issue contains the first papers of Processes and is intended to highlight a diverse set of topics related to process technology for the chemical, materials, biochemical, pharmaceutical and biomedical industries. To enhance the impact of these industries on society, process innovation that allows large-scale manufacturing is essential for both established and emerging technologies. The scope of this special issue includes, but is not limited to: chemical and biochemical reaction processes: mixing, fluid processing and heat transfer systems; mass transfer, separation and purification processes; integrated process design and scale-up; and process modeling, simulation, optimization and control.